Consumption, Media and the Global South Aspiration Contested - Iqani, Mehita; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
What does consumption in the global south signify, and how are its complexities communicated in media discourses? This book looks at the media representation of consumer culture in Africa, China, Brazil and India through case studies ranging from celebrity selfies, to travel websites, news reports and documentary film.
Keywords: Culture -- Study and teaching; Communication; Industries; Area studies; Cultural and Media Studies; Regional and Cultural Studies; Media and Communication; Media Studies; Area Studies; Industries; Electronic books